The Poetics of Grief and Healing in Nadin Amizah’s ‘Bertaut’ : A Stylistic Analysis - Nur Abqori Salma; Otong Setiawan Djauhari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the intricate relationship between grief and healing as depicted in Nadin Amizah's song